2021
DOI: 10.26717/bjstr.2021.38.006226
|View full text |Cite
|
Sign up to set email alerts
|

"Comparative Efficacy of Tocotrienol and Tocopherol for their Anti Diabetic Effects"

Abstract: Background: Diabetes is a chronic metabolic disorder and a Global health problem. Lifestyle modifications along with addition of miro nutrients and vitamin supplementation can be helpful to delay the occurrence of its life-threatening complications. Therefore, this systematic review was carried out to identify the comparative role of tocotrienol and tocopherol isoforms of antioxidant vitamin E for diabetic patient management.Research Question: Is tocotreinol has better anti diabetic effects as compared to toco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…It has been shown that tocotrienol helps to maintain glycemic levels in patients with DM and delay the appearance of diabetic complications due to its antioxidant, antiinflammatory, antihypertensive and fibrolytic properties [107]. Vitamin E therapy for DN has been investigated using both oral vitamin E protocols and vitamin E-coated hemodialysis and has shown promising results in the secondary prevention of cardiovascular diseases, as well as immune and hematological complications [95,108].…”
Section: Vitamin Ementioning
confidence: 99%
“…It has been shown that tocotrienol helps to maintain glycemic levels in patients with DM and delay the appearance of diabetic complications due to its antioxidant, antiinflammatory, antihypertensive and fibrolytic properties [107]. Vitamin E therapy for DN has been investigated using both oral vitamin E protocols and vitamin E-coated hemodialysis and has shown promising results in the secondary prevention of cardiovascular diseases, as well as immune and hematological complications [95,108].…”
Section: Vitamin Ementioning
confidence: 99%
“…These results show that D. salina has antioxidant properties by reducing markers of oxidative degradation and increasing antioxidant capacity exclusively in the liver. Moreover, a-tocopherol in plasma was increased suggesting that D. salina could protect against damage from free radicals [ 209 ]. Furthermore, D. salina has been reported to contain β-carotene and bioactive peptides that exhibit antioxidant activities.…”
Section: Effect Of Microalgae On Diabetes Mellitusmentioning
confidence: 99%